Development Of Managerial Skills Of Pre-School Directors (Journal of Pharmaceutical Negative Results, 2023)
Significance of the article is determined by the need to develop modern layouts to the development of managerial skills of directors of pre-school education. The goal of the article is contained in the study of managerial potential of directors of pre-school institutions. The article presents theoretical and applied studies of experts in the field of teaching management on the most significant problems of pre-school education.